2020
DOI: 10.1002/cjce.23826
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of electrical resistance tomography to the analysis of fluid distribution in haemodialysis modules

Abstract: This work aims to explore the applicability of electrical resistance tomography (ERT) in the analysis of fluid distribution in haemodialysis modules, which is not straightforward due to the complex geometry of the hollow fibre bundles and the small sizes of the modules. On the other hand, ERT is potentially a suitable and convenient technique for investigation in this field due to its cost‐effectiveness and capacity to perform measurements in opaque systems. After a preliminary estimation of the fibre bundle l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Applicability of ERT has also been explored for the analysis of fluid distribution in haemodialysis modules, an intricate process due to the complex geometry of the hollow fiber bundles and small sizes of the modules. Here, reliable conductivity maps are obtained by placing the module vertically or horizontally [18]. Experimental data collected for liquid mixtures of different sodium chloride concentrations have further shown that the ERT technique is suitable for detecting concentration variations.…”
Section: Introductionmentioning
confidence: 99%
“…Applicability of ERT has also been explored for the analysis of fluid distribution in haemodialysis modules, an intricate process due to the complex geometry of the hollow fiber bundles and small sizes of the modules. Here, reliable conductivity maps are obtained by placing the module vertically or horizontally [18]. Experimental data collected for liquid mixtures of different sodium chloride concentrations have further shown that the ERT technique is suitable for detecting concentration variations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the different electrical features of the object in the sensitivity field, the ET techniques could be divided into electromagnetic tomography (EMT), electrical capacitance tomography (ECT), electrical impedance tomography (EIT), and electrical resistance tomography (ERT). Based on the principle of electromagnetic induction, the EMT can reconstruct the distribution state of the magnetic permeability for the medium in the sensitivity field [1][2][3][4][5][6]; Based on the principle of capacitance sensitivity, the ECT can reconstruct the distribution state of the dielectric constant for the medium in the sensitivity field [7][8][9][10][11][12][13][14][15][16][17]; Based on the principle of impedance sensitivity, the EIT can reconstruct the distribution state of the complex admittance for the medium in the sensitivity field [18][19][20][21][22][23][24]; Based on the principle of resistance sensing, the ERT can reconstruct the distribution state of the dielectric resistivity/conductivity for the medium in the sensitivity field [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Electrical tomography (ET) technology consists of 4 different branches, namely, electrical impedance tomography (EIT) [8][9][10][11][12][13][14], ERT [15][16][17][18][19][20], electrical capacitance tomography (ECT) [21][22][23][24][25][26][27], and electromagnetic tomography (EMT) [28][29][30][31][32][33], among which the ERT technology is a new generation of medical imaging technology and a simplified form of the EIT technology when only the change of conductivity/resistivity of the sensitive field is considered, having three outstanding advantages of functional imaging, no damage, and medical image monitoring. Compared with other monitoring methods, ERT technology has incomparable advantages in real-time monitoring and quantitative evaluation of critical respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%